2020
DOI: 10.1080/10408398.2020.1740644
|View full text |Cite
|
Sign up to set email alerts
|

Grapes and their derivatives in modulation of cognitive decline: a critical review of epidemiological and randomized-controlled trials in humans

Abstract: Grapes and their derivatives in modulation of cognitive decline: a critical review of epidemiological and randomized-controlled trials in humans With an increase in life expectancy, the incidence of chronic degenerative pathologies such as dementia has progressively risen. Cognitive impairment leads to the gradual loss of skills, which results in substantial personal and financial cost at the individual and societal levels. Grapes and wines are rich in healthy compounds, which may help to maintain homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“… 7 The effects of flavonoid-rich food have been reported (in both clinical and observational studies) to improve measures of cognition and mood, particularly in relation to reducing cognitive decline in older adults, 8 , 9 and evidence suggests flavonoid-rich soft fruits may be capable of delaying the progression of Alzheimer’s disease. 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 The effects of flavonoid-rich food have been reported (in both clinical and observational studies) to improve measures of cognition and mood, particularly in relation to reducing cognitive decline in older adults, 8 , 9 and evidence suggests flavonoid-rich soft fruits may be capable of delaying the progression of Alzheimer’s disease. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Grapes and blueberries are among the major fruit dietary sources of flavonoids, and they are high in 3 specific flavonoid subgroups; anthocyanins, flavan-3-ols, and flavonols. 10 Several other soft fruits high in flavonoids, such as blackcurrants and blackberries, show promising effects in mental and cognitive health in humans and animals. 9 , 10 However, the studies are limited in number compared with those that have been done on grapes and blueberries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Travica et al [ 23 ] also indicated that there was no consistent pattern of findings in healthy older adults, largely due to variations in dose, duration and other methodological factors. The only other review included of an anthocyanin-rich food (grapes) [ 24 ] indicated more promising conclusions stating that 200–550 ml/day of grape juice up to durations of six months was associated with improved cognitive performance, particularly for older adults in the early stages of cognitive decline. This bold conclusion was on the basis of only six RCTs assessing grape juice and cognition, and only three studies included older adults (the remaining studies in the review were of wine consumption for which the evidence showed that light-to-moderate wine; one to four glasses/day, was generally associated with improved cognitive performance).…”
Section: Reviews Of Specific Polyphenol- Rich Foods or Classesmentioning
confidence: 99%
“…This bold conclusion was on the basis of only six RCTs assessing grape juice and cognition, and only three studies included older adults (the remaining studies in the review were of wine consumption for which the evidence showed that light-to-moderate wine; one to four glasses/day, was generally associated with improved cognitive performance). Furthermore, the conclusions relating to dose, population and duration (see Table 2 ) are arguably a little overzealous in light of the small number of studies reviewed [ 24 ], and there was no systematic assessment of bias or quality. Interestingly, resveratrol was highlighted as a specific polyphenol which is a possible effector of the beneficial outcomes of grapes.…”
Section: Reviews Of Specific Polyphenol- Rich Foods or Classesmentioning
confidence: 99%